Direções identitárias da arte contemporânea: tensões e intenções do debate pós-moderno - Da Rolt, Clóvis (Universidade do Vale do Rio dos Sinos, 2012)
It is the aim of this investigation work to comprehend in a more thorough way, the making processes of contemporary art in the light of the phenomenon of increased interaction among cultures, which in the sphere of postmodern culture advances strongly tinged with issues of identity nature. Isolating art – in the modern form – and treating it as an autonomous and impervious to the world organism is unthinkable in the present time. Dissociated from a historical project and from universal assimilation principles, contemporary art corresponds to a new form of processing the aesthetic practices in the field of art, within a sphere which is demanding, from the part of the artists, moving about increasingly conflicting territories. Criticism against, confrontation and attempts to discredit contemporary art generally reflect a biased and idle partiality. These attitudes do not consider the set of changes that have been taking place since at least the mid 70’s and which are affecting the field of visual arts although at the same time causing it to be a privileged territory for the possibilities of reading about the different social spheres such as the cultural identity one. In order to realize this research project, a hermeneutic approach was used and the starting point has been the critique of History affirmative values, combined with some considerations about the concept fields of culture and identity. This structural unit brings along an analysis over the contemporary art conducted by new perspectives present in the postmodern culture critique, strongly based on the contextuality of experience, on the narrative of knowledge and on the inconsistency of the synoptical and teleological explanations on reality. This research work has been constructed through the approximation of bibliographic data, ethnographic elements and experiences in the field of art, always under the domain of a dialogic sensitivity which does not advocate the establishment of axiomatic positions and “principles” about science, thus allowing for the movement of text reconstruction itself through its reading to make statement possibilities of the unsaid. The itinerary outlined from these standards creates strains that are not easily managed bearing in mind the fact that the products generated by science are also constructed from a unique language system which regulates temporality, rhythm and assimilation processes not wholly revealed. The projection of culture as a field for political experiment brought into our time the need to understand its impact over the different spheres of social life. As one of such spheres, art absorbed the creative, deconstructive and resignificant possibilities which form part of a project that aims at resetting the value of culture upon the deterioration of modern age. From this view the eschatological and suicidal irruptions of art lose strength as it takes the position of a text which enriches itself as it allows for other texts to impregnate it. It is through this perspective that art avoids the establishment of precise disciplinary limits and ventures into the pursuit of a meaning which will enable it to situate in social scenarios which renew themselves constantly.
Keywords: Identidade; Arte contemporânea; Pós-modernidade; Interação cultural; Identity; Contemporary art; Post-modernity; Cultural interaction; ACCNPQ::Ciências Humanas::Sociologia